Creative Economic Development in Islamic Economic Perspective on The Welfare of Society (Study on Ieko Queen Eceng Creamers, Sahabat Alam Kunciran Jaya, Tangerang) - Harisah Harisah; Inti Ulfi Sholichah; Sri Ramdhayanti; Aliyeva Patimat Shapiulayevna (Universitas Islam Lamongan, 2022)
The problem in this study inspires creative economic development activities aimed at improving the well-being of the water hyacinth craftsmen community in Situ Cipondoh. The water hyacinth plant can be transformed into a variety of marketable handicrafts. This has become a popular destination for both locals and visitors from other parts of the country. The purpose of this research is to determine the development of the creative economy in improving the economic welfare of water hyacinth craftsmen in Ieko Ratu Eceng Sahabat Alam, Situ Cipondoh, Kunciran Jaya, Tangerang in terms of Islamic economic aspects in Indonesia. This study employed interview techniques and field surveys with a sociological approach, with data collected through observation, interviews, and documentation. To get specific conclusions, it refers to literature studies based on the texts of the Quran and hadith and then analyzed using descriptive analysis techniques according to Islamic economics. Thus, this research shows that the creative economy development carried out by the Kunciran Jaya community through Ieko Ratu Eceng Sahabat Alam by utilizing water hyacinth into various kinds of handicrafts can improve the economic welfare of the Situ Cipondoh community. Besides that, in the view of Islamic economics, these activities are highly recommended and allowed because they are following the basic values of Islamic economics in Indonesia.